Financial management : principles and applications - Keown, Arthur J.; Martin, John D.; Petty, William; Scott Jr., J. David F. (Philippines : Pearson Education, 2005)
The "10 Principles of Finance" formerly "Axioms" provide the framework, or "the big picture" of finance, which ties the major concepts of the book together. This text constitutes a strong basis on which to build future studies and, for those students who are non-finance majors, a lasting understanding in the fundamentals of finance.
Part 1. The scope and environment of financial management -- Part 2. Valuation of financial assets -- Part 3. Investment in long-term assets -- Part 4. Capital structure and dividend policy -- Part 5. Working-capital management and special topics in finance -- Part 6. Special topics in finance .
Financial management :, Financial
Includes index.
Keywords: ECONOMICS